2023
DOI: 10.4103/jispcd.jispcd_157_22
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions toward healthcare and dental care services among parents and caretakers of people with intellectual disability (PWID)—A questionnaire study

Abstract: A BSTRACT Aim and Objective: In Malaysia, there was lack of local evidence on the perception of parents/caretakers of people with intellectual disabilities (PWID) about healthcare. Thus, this study aims to assess the perceptions toward healthcare services of parents or caretakers for PWID. Materials and Methods: Online survey using Google Forms was conducted on parents/caretakers of PWID who attended the special care dentistry clinic and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…PWID are often associated with mobility impaired, which found medical facilities and services more inaccessible. [ 16 ] Other studies showed similar findings in which weekly and monthly barriers to health care were experienced by a higher percentage of disabled people. [ 17 ] In order to overcome this barrier, parents use public transport to save time to find parking.…”
Section: Discussionmentioning
confidence: 66%
“…PWID are often associated with mobility impaired, which found medical facilities and services more inaccessible. [ 16 ] Other studies showed similar findings in which weekly and monthly barriers to health care were experienced by a higher percentage of disabled people. [ 17 ] In order to overcome this barrier, parents use public transport to save time to find parking.…”
Section: Discussionmentioning
confidence: 66%